Cross-boundary cooperation in wildfire management during the custodial management period of the US Forest Service: A case study of the eastern Cascades of Oregon, USA, 1905–1945. (April 2023) - Steen-Adams, Michelle M.; Charnley, Susan; Adams, Mark D.O.
Abstract: In the U.S., federal, tribal, state, local, and private land management entities seek to implement a wildfire management strategy that spans large spatial extents and multiple ownerships to achieve wildfire risk reduction and forest restoration. This strategy requires cross-boundary cooperation. Cooperative cross-boundary forest management is not new; yet little case study research has documented historical examples. This study provides insight into how potentially overlooked models of cross-boundary cooperation of the past may be applicable to renewed cross-boundary cooperation today. We examined cooperation during the custodial management period (1905–1945) of Forest Service history. This study identifies the governance institutions, partner roles, and practices that promoted the establishment and durability of cross-boundary cooperation under two governance models adopted by the Forest Service and partners. The models are: cooperative federalism, for partnering with state and private landowner local entities – forest protective associations (FPAs); and federal interagency cooperation, for partnering with the Bureau of Indian Affairs Forestry Division, historically responsible for managing tribal lands. Using case study methods, we examined two examples of each model from the eastern Cascades of Oregon, USA. Two governance characteristics promoted durable cooperation, regardless of model: (1) the development of a bundle of cooperation-focused institutions (cross-organizational policy alignment; headquarters-level cooperative policies, laws, and/ or interagency agreements; unit-level cooperative agreements) that linked multiple Forest Service administrative levels (agency headquarters, local unit) to those of partner entities; and (2) the performance of a diversity of partner roles— operating at both headquarters and local levels — that enabled management entities to offset capacity constraints. Several governance characteristics promoted cooperation in the model that engaged private landowners (cooperative federalism). These were: the state-granted authorities of a special purpose district, whereby self-organized FPAs garnered resources and developed and enforced cooperative practices that coordinated upward with state and federal policies; recognition by the state and Forest Service of authorized, local entities that represented private landowners (FPAs) as essential partners; an administrative structure for state transfer of federal funding to local entities, resulting in cost-sharing; and the state's performance of the roles of cost-sharing administrator and liaison between Forest Service and local entities. We suggest that the more partners can integrate these features into cross-boundary wildfire management cooperation today, the better its chances of establishment and durability. Highlights: US Forest Service cross-boundary cooperation originated in the early 20th century. Cooperation required institutions at headquarters and unit administrative levels. State roles as intermediary and administrator enabled federal-private cooperation. Cost-sharing among federal and private entities enabled fire management cooperation. Special purpose districts enabled private landowner involvement in forest governance.